Gem of a ghost [large type] - Jaffarian, Sue Ann, 1952- (Jaffarian, Sue Ann, 1952- Ghost of Granny Apples mystery., 2012)
Emma Whitecastle would rather spend time with her boyfriend than help Joanna Reid get rid of her husband's ghost. But when she finds out Joanna's daughter has broken her engagement and attempted suicide, Emma and Granny Apples, the spirit of her pie-baking great-great-great-grandmother, are compelled to investigate. The multifaceted mystery unfolds in Hollywood, where Emma and Granny unearth a clue hidden in a haunted diamond.